A generic in-place transformation-based approach to structured model co-evolution - Meyers, Bart; Wimmer, Manuel; Cicchetti, Antonio; Sprinkle, Jonathan (Electronic Communications of the EASST, 2012)
In MDE not only models but also metamodels are subject to evolution. More specifically, they need to be adapted to correct errors, support new and/or update language features. The direct consequence of such evolutionary steps comprises the problem of managing the co-evolution of existing model instances, which may no longer conform to the new metamodel version. This model migration is intrinsically complex and results in a time-consuming and error-prone process if no adequate support is provided. For tackling this problem, we introduce a new technique to guide the user in solving migration issues in a step-wise manner. The aims are manifold, notably the simplification of the migration specification, the reduction of the effort for the evolver, the control of user intervention, and the optimization of the migration execution itself by allowing in-place adaptation of the existing instances.